Hour of the star - Amaral, Suzana
This Brazilian film is about a northeastern immigrant orphan in Brazil named Macabea, a religious reference to the Macabee, who moves to the big city in an attempt to escape economic and social poverty. Unfortunately, she struggles to little avail. She makes little progress in the way of improving her life because of her severe deprivation of social skills, hygiene, nutrition, and formal education.